Analisis Yuridis Tindak Pidana Kekerasan Seksual terhadap Anak (Studi Putusan Kasus Nomor 48/Pid.B/2019/PN Prn) - Adlin Herdiyansyah Putra; Iin Hot Prinauli Purba (CV Rewang Rencang, 2025)
This research entitled Juridical Analysis of Sexual Violence Against Children (Case Study of Court Decision Number 48/Pid.B/2019/PN PRN) aims to examine the forms of legal protection for child victims of sexual violence under Indonesian law and to analyze the judicial considerations and verdict of the judge in handling the case. This study employs a normative juridical method with a library research approach, using secondary data such as statutory regulations, legal doctrines, court decisions, and relevant academic literature. The findings indicate that legal protection for child victims of sexual violence has been regulated under several national legal instruments, including the 1945 Constitution, the Indonesian Penal Code, the Criminal Procedure Code, the Child Protection Act, the Domestic Violence Act, the Witness and Victim Protection Act, and the Sexual Violence Crime Act. In case decision Number 48/Pid.B/2019/PN PRN, the panel of judges sentenced the defendant to seven years of imprisonment under Article 46 of the Domestic Violence Act in conjunction with Article 65 of the Penal Code, based on juridical, factual, and sociological considerations. However, the verdict still focused on repressive measures, as it did not include restitution or rehabilitation for the victim, which are mandated by the Witness and Victim Protection Act and the Sexual Violence Crime Act.